The Role of HRM in Talent Management in British Gas - Kiang, Tay Kiat (Digital Repository of Theses, 2026)
The modern energy sector faces significant challenges in attracting, retaining, and managing skilled talent amidst rapidly evolving market demands. This study examines how British Gas has transformed its Human Resource Management (HRM) practices to address these talent management challenges. The research explores the shift from traditional administrative HR roles to a strategic function that integrates technology, analytics, and employee-centric approaches. The study aims to answer three key questions: What changes have been made in British Gas HR to address talent management challenges? To what extent does HR transformation at British Gas focus on talent management to address these challenges? Moreover, how can British Gas improve its talent management strategies to enhance employee engagement? Employing an interpretivist approach, this qualitative study collected data through in-depth interviews with 10 employees from various departments at British Gas. Findings reveal that HR transformation at British Gas emphasizes personalized employee development, inclusive workplace culture, and leveraging data-driven decision-making to enhance talent retention and engagement. Key improvements include initiatives in diversity, open feedback mechanisms, and skill development programs. The research concludes that British Gas’s HR transformation effectively addresses talent management challenges by fostering adaptability, employee satisfaction, and strategic alignment. Key recommendations include enhancing learning opportunities, integrating adaptive strategies for evolving market needs, and continuously improving HR policies to maintain competitiveness. This study contributes to HRM literature by demonstrating the value of strategic HR transformation in promoting organizational resilience and success in the energy sector.